2012
DOI: 10.4102/ojvr.v79i1.385
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine trypanosomosis and its vectors in two districts of East Wollega Zone, Ethiopia

Abstract: Trypanosomosis is a parasitic disease that causes serious economic losses in livestock, especially in sub-Saharan countries. This study was conducted from October 2010 to March 2011 in the Diga and Sasiga districts of the East Wollega zone in western Ethiopia to determine the prevalence of bovine trypanosomosis and its vectors. A total of 386 blood samples were collected from randomly selected animals. Packed cell volume (PCV) was determined and samples were examined for the presence of trypanosomes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 5 publications
9
12
1
Order By: Relevance
“…(p>0.05). The finding of higher prevalence of infection in the poor body condition animals (7.3%) than the good body condition ones (3.8%) corroborates the reports of Tafese et al (2012) that good body conditioned animals had less infection with trypanosome when compared with the poor conditioned ones. There was no significant difference (p>0.05) between the prevalence of infection in good and poor body conditioned animals.…”
Section: Discussionsupporting
confidence: 88%
“…(p>0.05). The finding of higher prevalence of infection in the poor body condition animals (7.3%) than the good body condition ones (3.8%) corroborates the reports of Tafese et al (2012) that good body conditioned animals had less infection with trypanosome when compared with the poor conditioned ones. There was no significant difference (p>0.05) between the prevalence of infection in good and poor body conditioned animals.…”
Section: Discussionsupporting
confidence: 88%
“…The apparent densities of Glossina species was 0.24 and 1.09 fly/trap/day in Gambela and Abobo districts respectively. This result is in agreement with different reports in western, south, south western and north western part of the country: 1.45 and 0.58 fly/trap/day in two districts of East Wollega zone, western Ethiopia [31], and 1.14 fly/trap/day in Southern Rift Valley of Ethiopia [32]. The sex category indicated male and female tsetse fly account for 36.70% and 63.30% of total caught Glossina species, respectively.…”
Section: Citationsupporting
confidence: 94%
“…This study finding is also in line with that of Bitew et al (2011), Teka et al (2012) and Fayisa et al (2015), who reported that statistically significant association between prevalence of trypanosomosis and body condition in cattle. However, in contrary to this Abebayehu et al (2011), Bekele and Nasir (2011), Tafese et al (2012), Dawit et al (2015) and Kitila et al (2017) reported that body condition of cattle was not significantly associated with the prevalence of trypanosomosis in cattle.…”
Section: Discussionmentioning
confidence: 85%